Laser Capture Micro-Dissection – A Premium Tool in Oral and Maxillofacial Pathology - Mishra, Pallavi; Mohanty, Aishwariya; Panda, Abikshyeet (International Journal of Psychosocial Rehabilitation, 2020)
The dawn of new technologies has enabled deeper insight into processes at subcellular levels, which ultimately improves diagnostic procedures and patient outcomes. Microdissection has greatly contributed to rapid growth in several areas, such as gene expression analysis, proteomics, genomics, and metabolomics. Laser capture microdissection (LCM) as a method of procuring subpopulations of cells under direct visual inspection plays a vital role in these areas. There is ample evidence to substantiate the utility of LCM in understanding the underlying molecular mechanism involving an array of oral physiological and pathological processes. This review provides the indispensable application of LCM in various oral disease from the perspective of an oral pathologist.